Unraveling the pathogenesis of Barrett’s esophagus and esophageal adenocarcinoma: the “omics” era - Barchi, Alberto; Dell’Anna, Giuseppe; Massimino, Luca; Mandarino, Francesco Vito; Vespa, Edoardo; Viale, Edi; Passaretti, Sandro; Annese, Vito; Malesci, Alberto; Danese, Silvio; Ungaro, Federica (Frontiers in Oncology, 2025)
Barrett’s esophagus (BE) represents a pre-cancerous condition that is characterized by the metaplastic conversion of the squamous esophageal epithelium to a columnar intestinal-like phenotype. BE is the consequence of chronic reflux disease and has a potential progression burden to esophageal adenocarcinoma (EAC). The pathogenesis of BE and EAC has been extensively studied but not completely understood, and it is based on two main hypotheses: “transdifferentiation” and “transcommitment”. Omics technologies, thanks to the potentiality of managing huge amounts of genetic and epigenetic data, sequencing the whole genome, have revolutionized the understanding of BE carcinogenesis, paving the way for biomarker development helpful in early diagnosis and risk progression assessment. Genomics and transcriptomics studies, implemented with the most advanced bioinformatics technologies, have brought to light many new risk loci and genomic alterations connected to BE and its progression to EAC, further exploring the complex pathogenesis of the disease. Early mutations of the TP53 gene, together with late aberrations of other oncosuppressor genes (SMAD4 or CKND2A), represent a genetic driving force behind BE. Genomic instability, nonetheless, is the central core of the disease. The implementation of transcriptomic and proteomic analysis, even at the single-cell level, has widened the horizons, complementing the genomic alterations with their transcriptional and translational bond. Increasing interest has been gathered around small circulating genetic traces (circulating-free DNA and micro-RNAs) with a potential role as blood biomarkers. Epigenetic alterations (such as hyper or hypo-methylation) play a meaningful role in esophageal carcinogenesis as well as the study of the tumor micro-environment, which has led to the development of novel immunological therapeutic options. Finally, the esophageal microbiome could be the protagonist to be investigated, deepening our understanding of the subtle association between the host microbiota and tumor development.